ANALYSIS OF ONLINE ACADEMIC INFORMATION SYSTEMS (SIAKAD) USING COBIT 2019 FRAMEWORK (CASE STUDY OF STMIK DHARMA WACANA METRO) - Herlida, Dian Rama; Syaputra, Muhammad Adie (Jurnal TAM (Technology Acceptance Model), 2024)
STMIK Dharma Wacana Metro as a university that has implemented information technology in its business processes, with information technology it is hoped that it can advance and become a supporter in achieving business process goals. In supporting and carrying out its business processes, STMIK Dharma Wacana Metro City has used the Academic Information System (SIAKAD), which functions in managing academic services, finance and accounting, libraries, student services, collaboration, research and publications. Academic information system management that is not well managed will have an impact on low service quality, which can affect the level of stakeholder trust in the institution. Thus, there is a need for Information Technology Governance Analysis in Academic Information Systems (SIAKAD). The governance audit was carried out using the COBIT 2019 framework with the Delivery Support and Service (DSS) domain. Audit results using the COBIT 2019 framework are used to find out how SIAKAD performs in organizations which will later be able to provide recommendations to support business processes